Derivation of the Uncontrolled Donation after Circulatory Determination of Death Protocol for New York City - Wall, S. P.; Kaufman, B. J.; Gilbert, A. J.; Yushkov, Y.; Goldstein, M.; Rivera, J. E.; O’Hara, D.; Lerner, H.; Sabeta, M.; Torres, M.; Smith, C. L.; Hedrington, Z.; et al. (American journal of transplantation, 2011)
Evidence from Europe suggests establishing out‐of‐hospital, uncontrolled donation after circulatory determination of death (UDCDD) protocols has potential to substantially increase organ availability. The study objective was to derive an out‐of‐hospital UDCDD protocol that would be acceptable to New York City (NYC) residents. Participatory action research and the SEED‐SCALE process for social change guided protocol development in NYC from July 2007 to September 2010. A coalition of government officials, subject experts and communities necessary to achieve support was formed. Authorized NY State and NYC government officials and their legal representatives collaboratively investigated how the program could be implemented under current law and regulations. Community stakeholders (secular and religious organizations) were engaged in town hall style meetings. Ethnographic data (meeting minutes, field notes, quantitative surveys) were collected and posted in a collaborative internet environment. Data were analyzed using an iterative coding scheme to discern themes, theoretical constructs and a summary narrative to guide protocol development. A clinically appropriate, ethically sound UDCDD protocol for out‐of‐hospital settings has been derived. This program is likely to be accepted by NYC residents since the protocol was derived through partnership with government officials, subject experts and community participants. This article reports on development of New York City's Uncontrolled Donation after Circulatory Determination of Death protocol. See editorial by Hanto and Veatch on page 1351.